Adult Lumbar Scoliosis : A Clinical Guide to Diagnosis and Management - Klineberg, Eric O. (Springer International Publishing : Imprint: Springer, 2017)
Providing a sound definition and review of the pertinent treatment goals for the management of adult lumbar scoliosis, this practical and comprehensive guide covers everything from pre-operative evaluation and radiography to post-operative management and complications. Both non-operative and operative strategies are presented, including minimally invasive techniques, decompression, anterior release, spinal osteotomy, biologics, and proximal and distal fixation, with an emphasis on clinical guidelines and management outcomes. The impact and prevention of complications following treatment are also discussed, including the prevention of proximal junctional kyphosis. Concluding with an examination of future directions for research and clinical treatment strategies, the comprehensive approach of this book provides the orthopedic surgeon, neurosurgeon and spinal practitioner with the most current evidence and expert thought about the evaluation and management of adult lumbar scoliosis.
Keywords: Medicine.; Orthopedics.; elektronické knihy; electronic books